Your library: a successful service center for a successful faculty (Journal of EAHIL, 2017)
Yesterday there was disastrous storm in my hometown. Many cellars and garages were flooded including some ofthe library’s storerooms. But thankfully many people helped out of nowhere. There’s a saying in Germany: manyhands make light work and so the storm passed over quite easily. In a rapid changing environment you need to adaptand develop unexpected strengths and skills. That holds very much true for the library itself. The thunder storm inour book world is that there are no books left. That is good news for disasters but bad news for our profession. Justto change to digital media or gadgets will not work in all cases. Our principal financing comes from the faculty andthe scientists are both specifically demanding and library denying. So we had the idea to develop a strategy forresearch support in order to serve our scientists even better. We came up with the following ideas, measures and stepsto rebuild the library to a successful service center for a successful faculty. To accomplish our tasks we tried to thinkfrom a strict researcher perspective.